O prepovedi retroaktivnosti predpisov - Šinkovec, Borut (Pravni letopis, 2013)
The state with the rule of law is based on two basic elements: the very existence of written law, which equates with legal certainty, and on the confidence in this (existing) law, i.e. the confidence in existing law as it is at the time when it is applied to have the consequences and effects as provided by it in advance. Therefore, possible later changes of the law (or a new law) may have no effect on previous legal actions under the previous law. Otherwise, this would bring about real (inadmissible) retroactive effect of law. Remarkably, many laws often may only have the effect of false (seeming) retroactivity, without true retroactive effect. Such for instance is often the case when it comes to laws, referring to labour law, employment law or family law, etc. In such cases, no true retroactive effect of law is involved. Such laws only have the so called ex nunc effect in the future, from now on. Noviolation of inadmissible retroactivity is involved. In fact, it is often difficult to distinguish clearly between the cases of real (true) and cases of but false (seeming) retroactivity. Only if the legislator is sufficiently meticulous abot this, also the former element or principle of both principles mentioned above, which a state of law duly requires, is ensured.
Keywords: pravna država; pravna načela; zakonodaja